PENGARUH PELATIHAN BERPIKIR POSITIF PADA EFIKASI DIRI AKADEMIK MAHASISWA (STUDI EKSPERIMEN PADA MAHASISWA FAKULTAS PSIKOLOGI UNDIP SEMARANG - Dwitantyanov, Aswendo; Hidayati, Farida; Sawitri, Dian Ratna (Jurnal Psikologi, 2010)
Academic self-efficacy is individual conviction to be up against academic duty assignment accords that expected. Academic self-efficacy motivated student for ductile and persistent in finalizing college task, up to aim, and settles $emerging interference (Bandura, 1997, p. 117). Positive thinking helps college student to face situations that evoke stress in study and makes college student to focus on the positive things. Therefore, positive thinking often used to determinant of high in academic self-efficacy, because it’s making college student focus successful possibility in academic while stress gristle situation (Kivimaki, et al, 2005, p. 413). Methodology: This research intent to test effect of positive thinking training to step up academic self-efficacy at college student. This research is done on 21 first year college student undergraduate, they have never been followed positive thinking training thinks before all, and they has academic self-efficacy low or moderate category. They agglomerated in two groups, which is experiment group and control group. Hypothesis that proposed in this research which is there is difference of academic self-efficacy at experiment and control groups. This research used Randomized Pretest-Posttest Control Group Design. Positive thinking training is given up to three meeting. Data collecting is done by use of observation method, interview, and academic self-efficacy scale for college student. Results: Hypothesis testing result by use of Independent Sample t-test yields value of p (0,000) < 0,05. It points out that there is significantly difference of academic self-efficacy score between experiment and control groups after treatment. Thus, positive thinking can be one of the ways to increase academic self-efficacy at college student. Conclusions: There is effect of positive thinking training to academic self-efficacy at first year college student at sychology faculty of Diponegoro University on Semarang.Kata Kunci : Positive thinking training, academic self-efficacy, college studentPermalink :